Inclusive education : a systematic perspective - Howley, Aimee (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"This book answers two questions: What does the implementation of inclusive education require of a system of education and all parts of the system? How do various parts of the education system act on their commitment to inclusive educational practice? Decades after major legislation (i.e., the Civil Rights Act, the Elementary and Secondary Education Act, and the Education for All Handicapped Children Act) made high-quality education a fundamental right for all children in the United States, the dream of diverse, inclusive, democratic schooling has yet to be realized. Nevertheless, some classrooms, schools, districts, states, and universities have made progress. Inclusive Education: A Systematic Perspective explores the theoretical implications of inclusive practice as well as illustrative case studies and evaluation findings from states, educator preparation programs, districts, and schools that have reframed their work around the principles of inclusive practice. Whether these organizations position the work as "social justice education," "culturally responsive teaching," or "inclusion," their efforts lead in the same direction-toward higher quality and more equitable education for all. The chapters will be relevant to graduate students, faculty members, and education leaders, at all levels, who seek a comprehensive overview of the commitment and practice of "inclusive education". Chapters vary in their approaches to the topic, some presenting theoretical underpinnings, others describing practices or programs at particular sites, others reporting findings from empirical studies, and edited interviews with state and district leaders of inclusive-education initiatives. The book explores why inclusion is important and how it can be accomplished"--